2021
DOI: 10.3389/fphar.2021.748740
|View full text |Cite
|
Sign up to set email alerts
|

CXCR7 Antagonism Reduces Acute Lung Injury Pathogenesis

Abstract: Loss of control in the trafficking of immune cells to the inflamed lung tissue contributes to the pathogenesis of life-threatening acute lung injury (ALI) and its more severe form, acute respiratory distress syndrome (ARDS). Targeting CXCR7 has been proposed as a potential therapeutic approach to reduce pulmonary inflammation; however, its role and its crosstalk with the two chemokine receptors CXCR3 and CXCR4 via their shared ligands CXCL11 and CXCL12 is not yet completely understood. The present paper aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…ACKR3/CXCR7 is ubiquitously expressed to various extent by circulating immune (monocytes, macrophages, [ 28 ] T-lymphocytes [ 190 ], B-lymphocytes [ 191 ], neutrophils [ 90 , 91 , 92 ]) and vascular cells (endothelium [ 27 ]) and also cells constituting the organs that these blood vessels perfuse (e.g., myocardium [ 26 ], brain [ 30 , 32 , 192 , 193 ]). Therefore, ACKR3/CXCR7 may elicit a cell- and organ-specific functional response [ 46 ], which cannot be restricted specifically to platelets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACKR3/CXCR7 is ubiquitously expressed to various extent by circulating immune (monocytes, macrophages, [ 28 ] T-lymphocytes [ 190 ], B-lymphocytes [ 191 ], neutrophils [ 90 , 91 , 92 ]) and vascular cells (endothelium [ 27 ]) and also cells constituting the organs that these blood vessels perfuse (e.g., myocardium [ 26 ], brain [ 30 , 32 , 192 , 193 ]). Therefore, ACKR3/CXCR7 may elicit a cell- and organ-specific functional response [ 46 ], which cannot be restricted specifically to platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils substantially aggravate HIT-associated thrombotic complications [ 77 ]. Neutrophils express ACKR3/CXCR7 [ 90 , 91 ], the antagonism of which regulates pulmonary injury associated with acute inflammation [ 92 ]. However, we observed that the CXCR7-agonist reduces HIT-IgG-induced human neutrophil activation, particularly the activation of CD11b in the Mac-1 complex.…”
Section: The Dichotomy Of Cxcr4 and Ackr3/cxcr7 In Plateletsmentioning
confidence: 99%
“…ACT-1004-1239 is an orally available, potent, and selective first-in-class CXCR7 antagonist that showed efficacy in preclinical animal models of multiple sclerosis ( Pouzol et al, 2021a ) and acute lung injury ( Pouzol et al, 2021b ), and had a favorable clinical profile following single- ( Huynh et al, 2021b ) and multiple-dose ( Huynh et al, 2021a ) administration. In context of drug development, identification of metabolites and metabolic pathways of a drug is of utmost relevance.…”
Section: Discussionmentioning
confidence: 99%
“…ACT-1004-1239 is an orally available, potent, selective, insurmountable, small-molecule CXCR7 antagonist ( Richard-Bildstein et al, 2020 ). Preclinically, ACT-1004-1239 showed dose-dependent efficacy in various animal models such as of multiple sclerosis ( Pouzol et al, 2021a ) and acute lung injury ( Pouzol et al, 2021b ) using its ligands CXCL11 and CXCL12 as biomarker of target engagement. Dose-dependent increases in CXCL11 and CXCL12 plasma concentration were associated with a reduction in immune cell infiltrates into the central nervous system ( Pouzol et al, 2021c ) or the bronchoalveolar space ( Pouzol et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Such integrative approach accelerates clinical development ( Muehlan et al, 2018 ). Huynh et al combine this innovative method with in vitro studies in order to characterize ADME in humans with the use of rat samples for metabolite structure elucidation of major human metabolites, and to identify human enzymes involved in the metabolism of an orally available, promising new drug with proven efficacy in preclinical animal models of multiple sclerosis ( Pouzol et al, 2021a ) and acute lung injury ( Pouzol et al, 2021b ), and favorable clinical profile following single and multiple-dose ( Huynh et al, 2021a ; Huynh et al, 2021b ) administration. Results from their in vitro and in vivo studies highlight the relevance of preclinical investigations in supporting the identification of metabolites in humans, allowing determining potential successive clinical studies.…”
mentioning
confidence: 99%